OPPORTUNITIES IN OPPORTUNISTIC COMPUTING. - Conti, Marco; Kumar, Mohan (Computer (00189162), 2010)
The article discusses the many opportunities available in opportunistic network computing. Opportunistic networks follow the way humans interact and thus, tied closely with social networks and can use human relationships to produce better and trustworthy protocols. It opens an interesting way for research and development, and increases the potential for actual-life application issues. The worldwide use of mobile cell phones with integrated technology have created a big number of contact opportunities that have become key to opportunistic communications.